TOWARDS AN INTEGRATED CONTROL OF SESAME (SESAMUM INDICUM L.) CHARCOAL ROT CAUSED BY MACROPHOMINA PHASEOLINA (TASSI) GOID - M Ibrahim; A Abdel-Azeem (Arab Universities Journal of Agricultural Sciences, 2007)
Soil solarization in combination with fungal antagonists and soil amendments has been sub-jected to evaluation as a potential disease man-agement strategy for the control of charcoal rot of sesame caused by Macrophomina phaseolina (Tassi) Goid. Solarization alone or in combination with Trichoderma pseudokoningii and Emericella nidulans singly or in mixed inocula reduces dis-ease incidence from 30 % (control) to 80%, 91 %, 82 % and 85% respectively. It is noted that while pairing improved the biocontrols potentiality of E. nidulans by increasing the number of healthy plants in both unsolarized and solarized soils it leads to decrease in the biocontrol potentiality of T. pseudokoningii. On the other hand the combina-tion of solarization with soil amendment with Eu-calyptus powdered leaves showed a synergistic effect by increasing number of healthy plants from 65 % in amended unsolarized soil to 77 % in amended solarized soil.